Karakterisasi Kimia CMC (Carboxymethyl Cellulose) Umbi Ganyong - Selfa Dewati Samah; Renny Futery; Gustiarini Rika Putri; M. Ikhlas Armin (REACTOR: Journal of Research on Chemistry and Engineering, 2022)
Carboxymethyl Cellulose (CMC) a compound made from starch of tubers ganyong flour with added methanol, propanol and water. Four process involving alkalization process, karboksimetilasi, neutralization in the process of making the CMC. Carboxymethylization process involving alkazation process neutralization in the proess of making the CMC. Alkazation is reaction between cellulose and soda solution (alkaline) to become alkaline cellulose (cellulose is soluble in soda solution). Carboxymethylization is rection between alkaline cellulose and sodium chloro acetate compound to form sodium Carboxymethyl Cellulose (Na.CMC) which froms a viscous solution. Neutralization is solution neutralization process and the last prcess is the manufacture of CMC. Two processes were first made is Alkazation and Carboxymethylization by reacting 22 g NaOH and 20 g ClCH2COONa respectively. Acetic acid is added is used in the neutralization process, during the heating process in the oven. The overall results for each degree of substitution; pH; viscosity; water content; NaCl concentration; purity; Redemen of cellulose: Rendemen of CMC ganyong; 0.81; 8; 7 cP; 5% 2.01%; 97.99%; 2%; 98.5% respectively. CMC ganyong from the research that has been tested by FTIR spectra test results CMC ganyong can be seen in the picture there are similarities peaks that appears indicating CMC canna generated in this study have the same chemical molecules CMC commercially for food chemical codex is at 732 cm-1 while the peak of commercial CMC 725 cm-1 is carboxyl group and -CH. Based on the research results obtained, it can be concluded that the CMC is of good quality as a filler to make chemical bond stronger.